Multicentre, open label, randomised controlled trial comparing intermittent versus daily treatment for non-cavitary nodular/bronchiectatic Mycobacterium avium complex lung disease with rifampicin, ethambutol and clarithromycin (iREC): study protocol. Issue 1 (30th May 2019) - Nakagawa, Taku; Hashimoto, Hiroya; Yagi, Mitsuaki; Kogure, Yoshihito; Sekimizu, Masahiro; Saito, Akiko M; Ogawa, Kenji; Inoue, Yoshikazu
Abstract : Introduction: Standard treatment for nodular/bronchiectatic Mycobacterium avium complex lung disease (NB MAC-LD), excluding severe-status cases, differs between Japan and other countries. Internationally, three-drug combination intermittent treatment (three times a week administration) with macrolide, ethambutol and rifampicin is recommended, but a daily treatment regimen is recommended in Japan. To date, no randomised controlled study directly comparing intermittent treatment with daily treatment has been performed. The purpose of this study is to investigate the usefulness of intermittent treatment. Methods and analysis: A total of 140 patients diagnosed with NB MAC-LD in Japan will be randomly assigned, in a 1:1 ratio, to intermittent treatment group or daily treatment group, and three-drug combination therapy with clarithromycin, rifampicin and ethambutol will be continued for 1 year. The primary endpoint is the proportion of patients requiring modification of the initial treatment regimen. Secondary endpoints are adverse events, sputum culture conversion, time to sputum culture conversion, improvement of chest CT findings, change in health-related quality of life score and development of clarithromycin resistance. Ethics and dissemination: This trial was approved by the National Hospital Organisation Review Board for Clinical Trials (Headquarters). The results of this study will be reported at a society meeting or published in a peer-review journal.